Distance to market and farm-gate prices of staple beans in rural Nicaragua - Ayako Ebata; Pamela Velasco; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2015)
While smallholder market participation is seen as a catalyst for poverty alleviation, farmers in rural areas face a number of challenges in doing so. One of the most important factors is considered transaction costs related to transportation. Our study quantifies the benefits associated with improvement of rural road infrastructure by scrutinizing farm-gate prices of beans in rural Nicaragua. We find that the longer the distance and traveling time are to major commercial centers from farming communities, the less farm-gate prices producers receive. We find that a decrease in distance and traveling time by one unit is associated with an increase in farm-gate prices by 2-2.5 cents/qq. If infrastructure development can reduce travel time by 25%, an average farm would increase its annual revenue from beans by between 27.69 and 125.96 (between 4% and 18% of annual revenue today). Given that such infrastructure development affects all farmers and all crops, our findings suggest a larger implication at the sectorial level.
Keywords: O13; O18; Q11; 330; producer prices; Central America; transactions costs; transportation infrastructure